Move Over, Descartes! Neuroscience Says You’re Wrong. - Kathleen Taylor (Adult Education Research Conference, 2017)
Recent discoveries in neuroscience, cognitive science, philosophy of mind, and psychology contradict Descartes’ rejection of the body’s role in thinking. This presentation examines implications for adult learning.
Keywords: neuroscience and adult learning; embodied learning; emotion and learning; analogical learning